Edward D. McLaughlin, The Revised Statutes and Codes of the State of Washington, at 1042, § 6353 (1896) - (:unkn) unknown (My University, 1883)
Sale of Toy Pistols to Children, It shall be unlawful for any person or persons to sell or offer for sale, any toy pistols within this state, and every person who shall sell, give, furnish, or cause to be furnished to any person under the age of sixteen years, any pistol, toy pistol or other pocket weapon, in which explosives may be used, shall be deemed guilty of a misdemeanor, and upon conviction, shall be fined in any sum not less than five, nor more than twenty-five dollars.
Keywords: TRANSFER - MINORS; TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES